Home Management of the Device Detected Atrial Fibrillation during COVID-19 Pandemic: A Case Report - Rakhimova, Idaliya; Khaibullin, Talgat; Smail, Yerbol; Urazalina, Zhanar; Koval`chuk , Vitalii; Abdrakhmanov, Ayan (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Patients with heart failure (HF) and implanted heart devices constitute a vulnerable category during the coronavirus disease –2019 (COVID-19) pandemic. The remote monitoring function allows the physician to detect atrial fibrillation (AF) in these patients and to prevent thromboembolic complications by prescribing anticoagulants. Under quarantine conditions, such patients can receive fully remote consultation and treatment, which will protect them from the risk of infection, and also reduce the burden on medical institutions. CASE REPORT: A 56-year-old man presented to the clinic with shortness of breath when climbing the second floor, moderate non-specific fatigue, general weakness, and a decrease in exercise tolerance. The patient received standard treatment for HF for at least 3 months (ACEI, beta blockers, MR antagonists, and loop diuretics) in individually selected adequate doses. ECG on admission showed a QRS of 150 ms, left bundle branch block (LBBB). Echo showed dilatation of all heart chambers, diffuse hypokinesis of the walls with akinesis of the apical, middle anterior LV segments, as well as hypokinesis of the basal, middle apical, and anterior septal segment of the LV. The ejection fraction was reduced to 35%. RV function is reduced. After a detailed discussion with the team, it was decided to do implantation of a cardioverter-defibrillator with resynchronization function, equipped with remote monitoring (Biotronik, and Home monitoring). Date of implantation is June 19, 2014. Due to the fact that the patient was connected to the remote monitoring system, May 5, 2020, he was diagnosed with asymptomatic AF. The episode lasted 1 min 22 s. On the following days of monitoring, episodes of AF were also recorded. The duration of the episodes ranged from a few seconds to 12 h/day. The patient received a doctor’s consultation through phone call, his risk of stroke was four when assessed using the CHA2DS2VASc scale. In treatment, it was recommended to add antiarrhythmic drugs (amiodarone 600 mg a day) and oral anticoagulants (rivaroxaban 20 mg × 1 time/day). Later, periodic IEGM showed absence of AF. CONCLUSION: In the context of the COVID-19 pandemic, health-care providers should rethink their approach to managing patients with implanted heart devices. Modern cardiovascular implantable electronic devices allow the physician to monitor the status of patients and immediately respond to situations requiring a change in treatment. Consultations can be carried out completely online.